Religion and Sustainability in Global Civil Society - Berry, Evan (Worldviews, 2014)
This paper presents basic empirical research about the role of religion and religious actors in the global politics of sustainability. Drawing on insights from three overlapping fields of study—environmental politics, religious transnationalism, and religion and ecology—this study analyzes data gathered through ethnographic interviews with representatives of religious non-governmental organizations at the 2012 United Nations Conference on Sustainable Development, known as Rio+20. These interviews asked respondents to discuss their understanding of the meaning, role, and position of religion within civil society efforts to address sustainability concerns. Content analysis of interview responses suggests that religious actors hold divergent views about the salience of religion to global sustainability politics. The central finding is that the boundary between religious and secular civil society groups is a permeable one.